First example of an octa-glycoconjugated magnesium(II)porphyrazine. Issue 4 (27th January 2016) - Klein, Thomas; Ziegler, Thomas
Graphical abstract: Highlights: First synthesis of an octa-glycoconjugated magnesium(II)porphyrazine. Physical properties and characterization by spectroscopy and spectrometry. Possible application as photosensitizer in photodynamic therapy. Abstract: Treatment of disodium maleonitriledithiolate with 1, 2:3, 4-di- O -isopropylidene-6- O -trifluoromethanesulfonyl-α-d -galactopyranose gives 2, 3-bis(6-deoxy-1, 2:3, 4-di- O -isopropylidene-6-thio-α-d -galactopyranos-6-yl)maleonitrile in 87% yield. Heating of the latter with magnesium bis(butan-1-olate) in butan-1-ol affords [2, 3, 7, 8, 12, 13, 17, 18-octakis(6-deoxy-1, 2:3, 4-di- O -isopropylidene-6-thio-α-d -galactopyranos-6-yl)porphyrazinato]magnesium(II) in 53% yield. The glycoconjugated porphyrazine has an absorbance maximum at 673 nm and is a candidate as photosensitizer for photodynamic therapy.